Bridging the gap: Student perceptions of blended learning's promise and reality in higher education - Rahman, Abdul; Syamsurijal Basri; Syamsuardi, Syamsuardi (Jurnal Inovasi Teknologi Pendidikan, 2025)
This study investigates students’ perceptions of their learning experiences in a blended learning environment. It seeks to describe: 1) students’ perceived learning effectiveness in blended learning, 2) key aspects of blended learning contributing to learning effectiveness, and 3) problems and constraints in blended learning. A cross-sectional survey design was employed, targeting undergraduate students from six departments and three different semester cohorts who had experienced blended learning. With a population of approximately 6.000 students, a sample of 509 students was selected using stratified random sampling to ensure proportional representation across departments and cohorts. Data were collected through a structured questionnaire and analyzed using descriptive statistics. Results indicate that while 60% of students strongly valued the flexibility to access materials anytime/anywhere, fewer than 40% reported effective self-paced learning or study planning. Interaction and collaboration were limited (25–38% agreement), and perceived impacts on motivation (27–35%) and material understanding (26–27%) were modest. Technical ability varied, with only 24% feeling highly competent in platform feature usage. Overall satisfaction was low (29%), aligning with suboptimal active engagement, interaction/collaboration, and perceived impacts. Findings suggest that blended learning implementation at this institution did not fully realize its potential for autonomy, collaboration, or enriched outcomes, highlighting the need for improved pedagogical design, user-friendly technology, and strategies to foster critical dialogue and self-regulation.